Overeducation, Overskilling and Job Satisfaction in Europe: The Moderating Role of Employment Contracts - Romina Giuliano; Benoît Mahy; François Rycx; Guillaume Vermeylen (Global Labor Organization (GLO), 2024)
This paper is the first to examine whether and how overeducation and overskilling, considered separately and in interaction, influence workers' job satisfaction at European level. It also investigates the moderating role of employment contracts. Our results, based on a unique pan-European database covering 28 countries in 2014, show that overeducation and overskilling reduce the probability of workers being satisfied with their jobs, but also that the drop in job satisfaction is almost double for genuinely overeducated workers (i.e. workers that are both overeducated and overskilled). These adverse effects on job satisfaction are found to be more pronounced among mismatched workers (whether overeducated, overskilled or both) on fixed-term rather than indefinite contracts.
Keywords: C21; J24; J28; J41; 330; Job Satisfaction; Overeducation; Overskilling; Labour Contracts; Europe